How to have a thought : a walk with Charles Darwin - Day, Nicholas, 1991- (Neal Porter Books/Holiday House, 2026)
"How do you work through a complicated idea, solve a tricky problem, or make a big discovery? Charles Darwin had a lot of ways to do it. He paced in circles and hit rocks with a stick. He studied the bones of his dinner. He even rode around the world on a boat called The Beagle. These methods may sound unorthodox, but they led him to some pretty great thoughts--and discoveries about the origins of life as we know it"--